Photo-response polymer network based on azo element and mechanical interlocking structure as well as preparation and application of photo-response polymer network

By combining the azo moiety and mechanical interlocking structure, the cis-trans-isomeric regulation of the azo moiety is used to solve the problem of mechanical properties of photoresponsive supramolecular materials under light, and the tensile properties of polymer networks are realized and resilience significantly changes, demonstrating novel functions and application potential.

CN119161553APending Publication Date: 2024-12-20ZJU HANGZHOU GLOBAL SCI & TECH INNOVATION CENT
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411037037.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

It is difficult to achieve rapid response and reversible adjustment of existing photoresponsive supramolecular materials under light stimulation, and the tensile properties and toughness of the materials do not significantly change under different light conditions.

Method used

Combining the azo moiety with a mechanical interlocking structure, the sliding ability of the azo moiety is regulated through the cis-trans isomerization of the azo moiety to build a polymer network, so that it changes sterically under irradiation of 365nm light source, thereby adjusting the tensile properties of the polymer and Mechanical properties.

Benefits of technology

The mechanical properties of polymer networks under light conditions are realized, and the tensile properties and toughness of the material are significantly changed, showing new functions and application potential, and are simple to operate and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161553A_ABST
    Figure CN119161553A_ABST
Patent Text Reader

Abstract

The invention discloses a photoresponse polymer network based on azo elements and a mechanical interlocking structure as well as a preparation method and application of the photoresponse polymer network. The photoresponse polymer network is obtained through reaction of raw materials including an azo element, polytetrahydrofuran, hexamethylene diisocyanate and a mechanical interlocking unit. The azo element is selected from at least one of compounds with the following structures: # imgabs0 #, wherein n is 1-10; mechanical interlocking unit with the following structure: # imgabs 1 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of intelligent response optical materials, and in particular to a photoresponsive polymer network based on azo motifs and mechanical interlocking structures, and a preparation method and application thereof. Background Art

[0002] Supramolecular polymers are a cross-disciplinary study of polymer science and supramolecular science. Traditional polymers are formed by covalent bonds, while supramolecular polymers are polymers assembled by non-covalent bonds between the subject and the object, and can exhibit properties similar to polymers under certain circumstances. The non-covalent bonds give supramolecular polymers some special properties, such as thermal, optical, electrical, and chemical responsiveness, stretch resistance, and self-healing. The properties of non-covalent bonds can also be used to reversibly regulate supramolecular polymers.

[0003] Azobenzene and its derivatives can be said to be the simplest and most widely studied optical switch compounds. The patent specification with publication number CN115403797A discloses a sliding ring supramolecular gel film with fast light response performance and a preparation method. The preparation method uses azobenzene and benzyl isocyanate co-functionalized acrylamide and β-cyclodextrin functionalized acrylamide as reaction monomers, forms a sliding host-guest cross-linking structure through pre-inclusion of azobenzene and cyclodextrin, and uses potassium persulfate to initiate free radical polymerization to form supramolecular polymers. Finally, the obtained polymer is precipitated with acetone, washed, and fully swelled, spread, and dried in water to obtain a gel film. The gel film has fast light response performance. Under 365nm light, it can bend quickly to 40° in the direction of the light source within 0.5s, and can realize film flipping and other movements under ultraviolet light; it also has a high tensile strength of 15MPa, an elongation at break of 150%, and a Young's modulus of 0.34MPa. The patent specification with publication number CN118063716A discloses an anti-fatigue mechanically interlocked photoresponsive supramolecular hydrogel and a preparation method. The preparation method uses (E')-N-(4-(4-(4-hydroxyazobenzene)butoxy)benzyl)acrylamide-functionalized cyclodextrin as a reaction monomer, forms a mechanically interlocked cross-linked structure by pre-inclusion of azobenzene and cyclodextrin, and then uses potassium persulfate to initiate free radical polymerization, and copolymerizes with acrylamide to form a mechanically interlocked supramolecular hydrogel. The hydrogel has rapid photoresponsiveness and can bend rapidly by 15° in the direction of the light source within 2 seconds under irradiation of 365nm; it also has a tensile strength of 722kPa and an elongation at break of 544%; under a tensile strain of 400%, after 30 cycles of stretching, its cyclic tensile stress remains stable.

[0004] Under ultraviolet (UV) light irradiation, the planar nonpolar trans isomer of azobenzene isomerizes to the metastable cis form, which is nonplanar, polar, and sterically hindered. The cis→trans isomerization occurs spontaneously and can be accelerated under visible (blue) light. Due to the highly reversible nature of the cis / trans photoswitch, azobenzene and its derivatives have applications in energy storage systems, switchable catalysis, controlled release, and photopharmacology. Summary of the invention

[0005] The present invention provides a photoresponsive polymer network based on an azo motif and a mechanical interlocking structure, and a preparation method and application thereof. The present invention combines an azo motif that changes the steric hindrance by light regulation with a slip ring system, and utilizes the cis-trans isomerism of the azo motif to regulate the sliding ability of the macrocycle in the mechanical interlocking unit, that is, the trans conformation slip ring can pass, while the cis conformation slip ring cannot pass, thereby achieving the effect of regulating the mechanical properties of the material (such as tensile properties, etc.) by light stimulation.

[0006] A photoresponsive polymer network based on an azo motif and a mechanical interlocking structure is obtained by reacting raw materials including an azo motif, polytetrahydrofuran, hexamethylene diisocyanate and a mechanical interlocking unit;

[0007] The azo group is selected from at least one of the compounds having the following structure:

[0008]

[0009] Wherein, n is 1 to 10, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10;

[0010] The mechanical interlocking unit has the following structure:

[0011]

[0012] The present invention combines the azo motif that changes the steric hindrance by light regulation with the mechanical interlocking unit, and utilizes the cis-trans isomerism of the azo motif to regulate the sliding ability of the macrocycle in the mechanical interlocking unit, so as to construct a novel polymer with optical adaptability in tensile properties. In the initial state, the azo motif in the polymer network is in the trans conformation, with less steric hindrance, the macrocycle can slide freely, and the mechanical properties of the polymer are weak; when the polymer network is irradiated with a 365nm light source, the azo motif is in the cis conformation, the steric hindrance increases, the sliding distance of the macrocycle is limited, and the mechanical properties of the polymer are improved.

[0013] The preparation method of the azo moiety may include:

[0014] The 4,4'-dihydroxyazobenzene, monomer I, potassium carbonate and solvent are mixed for reaction, and after the reaction, the solvent is removed, and the mixture is extracted and purified, and column chromatography is performed to obtain the azo moiety;

[0015] The monomer I is selected from at least one of the compounds having the following structure:

[0016]

[0017] Herein, n is 1 to 10, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10.

[0018] In the method for preparing the azo element, the usage ratio of 4,4'-dihydroxyazobenzene, monomer I, potassium carbonate and solvent can be 1 mmol: 1.2-1.5 mmol: 2-4 mmol: 4-8 mL.

[0019] In the method for preparing the azo element, the solvent may include at least one of N,N-dimethylformamide and water.

[0020] In the method for preparing the azo unit, the temperature of the mixing reaction can be room temperature to 140°C.

[0021] In the method for preparing the azo unit, the mixing reaction time can be 12 to 24 hours.

[0022] In the method for preparing the azo unit, the extraction solvent used in the extraction purification may include dichloromethane.

[0023] In the method for preparing the azo moiety, the eluent used in the column chromatography analysis may be dichloromethane and methanol. Furthermore, in the eluent, the volume ratio of the dichloromethane to the methanol may be 20:1.

[0024] The number average molecular weight of the polytetrahydrofuran may be 1000 to 2000 g / mol.

[0025] In the raw materials, the total molar number of hydroxyl groups of azo units, polytetrahydrofuran and mechanical interlocking units may be equal to the total molar number of NCO groups of hexamethylene diisocyanate.

[0026] In the raw material, based on the total molar number of azo moieties, polytetrahydrofuran and mechanical interlocking units as 100%, the proportion of the azo moieties may be 25% to 45%, and the proportion of the mechanical interlocking units may be 25% to 35%.

[0027] The method for preparing the mechanical interlocking unit may include:

[0028] The reactant 1 and the reactant 2 are mixed in a solvent for reaction, and the solvent is removed after the reaction is completed to obtain the mechanical interlocking unit;

[0029] The reactant 1 has the structure shown below:

[0030]

[0031] The reactant 2 has the structure shown below:

[0032]

[0033] In the method for preparing the mechanical interlocking unit, the solvent may include dichloromethane.

[0034] In the method for preparing the mechanical interlocking unit, the temperature of the mixing reaction may be 40-50°C, for example 45°C.

[0035] In the method for preparing the mechanical interlocking unit, the mixing reaction time may be 12 to 24 hours.

[0036] The preparation method of the reactant 1 may include:

[0037] 4-Hydroxybenzaldehyde and 5-bromo-1-pentanol react to obtain compound 3 having the following structure:

[0038]

[0039] Compound 3 reacts with 6-hydroxyhexylamine to obtain a Schiff base, which is reduced with sodium borohydride and then added with hydrochloric acid to produce a precipitate. The solid is separated from the solid and added to a saturated ammonium hexafluorophosphate solution, and extracted and purified to obtain the reactant 1.

[0040] The preparation method of the reactant 2 may include the following synthetic route:

[0041]

[0042] The preparation method of the reactant 2 may include the steps of:

[0043] (1) heptaethylene glycol reacts with p-toluenesulfonyl chloride to obtain intermediate 4;

[0044] (2) The intermediate product 4 reacts with 3,4-dihydroxybenzaldehyde to obtain the intermediate product 5, and the intermediate product 5 is reduced with sodium borohydride to obtain the reactant 2.

[0045] The present invention also provides a method for preparing the photoresponsive polymer network, comprising:

[0046] Under an inert atmosphere, an azo unit, polytetrahydrofuran, hexamethylene diisocyanate, a reaction solvent and a catalyst that can be added or not are mixed and reacted for a period of time, and then a mechanical interlocking unit is added to continue the reaction. The reaction mixture is vacuum dried to obtain the photoresponsive polymer network.

[0047] The inert atmosphere refers to an atmosphere that does not participate in the reaction, such as a nitrogen atmosphere.

[0048] The reaction solvent may be an organic solvent. Further, the organic solvent may include at least one of dichloromethane, tetrahydrofuran, acetonitrile and acetone.

[0049] The catalyst may include dibutyltin dilaurate.

[0050] In the method for preparing the photoresponsive polymer network, the reaction temperature may be 30 to 50°C.

[0051] The present invention also provides the use of the photoresponsive polymer network in photosensitive materials. The tensile properties of the photosensitive materials change with changes in light conditions, and the cis-trans configuration of the azo moiety can be regulated by changing the light conditions to control the sliding ability of the ring in the mechanical interlocking unit, thereby achieving the adjustment of the tensile properties.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] 1. The present invention creatively realizes the addition of azobenzene photosensitive structural units into a polymer network, and utilizes the reversible isomerization of azobenzene under light to make a switch for adjusting the sliding distance of the ring, so that the finally synthesized polymer network becomes an intelligent polymer material whose mechanical properties can be adjusted by light.

[0054] 2. The method for preparing a photoresponsive polymer network based on azo motifs and mechanical interlocking structures provided by the present invention is simple to operate, has a reliable route and is low in cost.

[0055] 3. The photoresponsive polymer network based on azo elements and mechanical interlocking structure provided by the present invention utilizes the photoresponsive mode to regulate the ring sliding distance, thereby adjusting the mechanical properties of the polymer material. The regulation mode is novel and highly immediate, and the material is expected to exhibit new functions and application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is the NMR comparison result of the mechanical interlocking unit and reactant 2.

[0057] Figure 2 Graph showing stress-strain test results of the polymer network A(a) of the present invention and the control polymer network A(b) in Example 1 before and after irradiation at a stretching rate of 100 mm / min.

[0058] Figure 3 Graph showing stress-strain test results of the polymer network B (a) of the present invention and the control polymer network B (b) in Example 2 before and after irradiation at a stretching rate of 100 mm / min.

[0059] Figure 4Graph showing stress-strain test results of the polymer network C(a) of the present invention and the control polymer network C(b) in Example 3 before and after irradiation at a stretching rate of 100 mm / min.

[0060] Figure 5 This is a diagram showing the swelling results of the polymer network C of the present invention in Example 4.

[0061] Figure 6 This is a graph showing the change in strain, Young's modulus, and toughness of the polymer network AC of the present invention before and after irradiation in Examples 1-3.

[0062] Figure 7 Graphs showing optical test results of azo elements and polymer networks, showing: (a) the azo photosensitive unit of Example 3 is left standing under light for 60 min, (b) the azo photosensitive unit of Example 3 is left standing in darkness for 60 min, (c) the azo photosensitive unit of Example 3 is left standing in a light / standing cycle, (d) the polymer network of Example 3 is left standing under light for 60 min, (e) the polymer network of Example 3 is left standing in darkness for 60 min, and (f) the polymer network of Example 3 is left standing in a light / standing cycle.

[0063] Figure 8 Graphs showing the results of cyclic stress-strain tests of the polymer network of Example 3 over a wide range of maximum application strains from 25% to 200%, wherein: (a)-(b) are graphs showing cyclic stretching curves of the polymer network C of the present invention before and after irradiation, and (c)-(d) are graphs showing energy dissipation values ​​and damping energy of the polymer network C of the present invention before and after irradiation calculated based on the cyclic stretching curves.

[0064] Fig. 9 Graphs showing the cyclic stress-strain test results of the control polymer network of Example 3 over a wide range of maximum application strains from 25% to 200%, wherein: (a)-(b) are cyclic stretching curves of the control polymer network C before and after irradiation, and (c) is a comparison of the damping energies of the polymer network C of Example 3 and the control polymer network C of Comparative Example 3 before and after irradiation, calculated based on the cyclic stretching curves.

[0065] Fig.10 The present invention is a schematic diagram illustrating the connection between the microscopic intramolecular mechanical bond movement and the macroscopic mechanical properties of the polymer network before and after illumination. DETAILED DESCRIPTION

[0066] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0067] In the present invention, the stress-strain curves are all measured at room temperature at a constant tensile rate of 100 mm / min. Young's modulus is determined by the initial slope of the stress-strain curve. Toughness is a parameter that characterizes the work required for fracture of each unit sample, and is calculated based on the area of ​​the region below the stress-strain curve (until fracture). Energy dissipation is calculated by integrating the area contained in the cyclic tensile curve. Damping capacity is defined as the ratio of dissipated energy (area enclosed by the loading and unloading curves) to the loading energy (area enclosed by the loading curve).

[0068] The number average molecular weight of the polytetrahydrofuran used in the following examples and comparative examples is 1000 g / mol.

[0069] Example 1

[0070] Synthesis of azo photosensitive unit (i.e. azo moiety):

[0071]

[0072] 4,4'-dihydroxyazobenzene (23.4mmol, 5g) was added to a 500mL round-bottom flask, 100mL N,N-dimethylformamide (DMF) was added to dissolve, followed by potassium carbonate (72.3mmol, 10.0g) aqueous solution, and finally 5-bromo-1-pentanol (56.8mmol, 9.4g) was added, and the reaction was carried out at room temperature for 24h. Thin layer chromatography TLC detection, if the reaction is complete, the reaction system is distilled under reduced pressure to remove the solvent, and then dichloromethane (60mL×3) is added to the system for extraction, the combined organic phase is dried over anhydrous sodium sulfate, filtered and distilled under reduced pressure, and separated by column chromatography, the eluent is dichloromethane / methanol (volume ratio 20 / 1), and an azo photosensitive unit (5.46g, 49%) is obtained.

[0073] The hydrogen nuclear magnetic results of the azo photosensitive unit of this embodiment are as follows:

[0074] 1 H NMR (600MHz, CDCl3) δ (ppm): 7.87-7.85 (m, 4H), 6.99-6.98 (m, 4H), 4.06-4.04 (m, 4H),3.71-3.69(m,4H),1.90-1.80(m,4H),1.67-1.66(m,4H),1.59-1.58(m,4H).

[0075] Synthesis of mechanical interlocking units:

[0076]

[0077] 4-Hydroxybenzaldehyde (50 mmol) and 5-bromo-1-pentanol (60 mmol) were added to a 500 mL round-bottom flask, 100 mL of acetonitrile was added to dissolve, and then potassium carbonate (100 mmol) aqueous solution was added to react at room temperature for 24 h. The reaction was stopped, the solvent was dried, and column chromatography was used to separate to obtain compound 3 having the structure shown below: Subsequently, compound 3 (20.0 mmol) and 6-hydroxyhexylamine (20.0 mmol) were added to a 100 mL round-bottom flask, 100 mL of methanol was added to dissolve, and the mixture was reacted at room temperature for 24 h. Sodium borohydride (40.0 mmol) was then added in batches and reacted at room temperature for 12 h. Hydrochloric acid solution (5.00 M) was added and filtered to obtain a white precipitate. The white precipitate was added to a saturated ammonium hexafluorophosphate solution. Dichloromethane (60 mL × 3) was then added to the system for extraction, and the combined organic phase was dried over anhydrous sodium sulfate, filtered, and then distilled under reduced pressure to obtain a mechanically interlocked unit guest molecule, i.e., reactant 1.

[0078] The H NMR results of the reactant 1 in this example are as follows:

[0079] 1 H NMR(600MHz,Acetone)δ(ppm):7.56-7.45(m,2H),7.05-6.95(m,2H),4.48(s,2H),4.13-3.99(m,2H ),3.61-3.50(m,4H),3.40-3.35(m,2H),1.92-1.85(m,2H),1.83-1.77(m,2H),1.62-1.37(m,10H).

[0080] Heptaethylene glycol (45 mmol) was added to a 100 mL round-bottom flask, 35 mL of tetrahydrofuran was added to dissolve, then sodium hydroxide aqueous solution (15 mmol) was added, and finally p-toluenesulfonyl chloride (70 mmol) was added, and the mixture was reacted at room temperature for 24 h. Thin layer chromatography (TLC) detection, if the reaction was complete, the reaction system was distilled under reduced pressure to remove the solvent, and then dichloromethane (60 mL × 3) was added to the system for extraction, the combined organic phase was dried over anhydrous sodium sulfate, filtered, and distilled under reduced pressure, and separated by column chromatography, the eluent was dichloromethane / methanol (volume ratio 20 / 1), and the intermediate product 4 was obtained:

[0081]

[0082] The intermediate product 4 (30.5 mmol) was added to a 500 mL round-bottom flask, and 35 mL of acetonitrile was added to dissolve it, followed by an aqueous solution of potassium carbonate (100 mmol), and finally 3,4-dihydroxybenzaldehyde (30.5 mmol) was added, and the reaction was carried out at room temperature for 24 h. Thin layer chromatography TLC detection, if the reaction is complete, the reaction system is distilled under reduced pressure to remove the solvent, and then dichloromethane (60 mL×3) is added to the system for extraction, and the combined organic phase is dried over anhydrous sodium sulfate, filtered, and distilled under reduced pressure, and separated by column chromatography, the eluent is dichloromethane / methanol (volume ratio 20 / 1), to obtain the intermediate product 5:

[0083]

[0084] The intermediate product 5 (19 mmol) was added to a 100 mL round-bottom flask, and 35 mL of tetrahydrofuran and 20 mL of ethanol were added to dissolve it. Then sodium borohydride (95 mmol) was added in batches and reacted at room temperature for 24 h. Thin layer chromatography TLC detection, if the reaction is complete, a small amount of water was added to quench the reaction. The reaction system was distilled under reduced pressure to remove the solvent, and ethyl acetate (60 mL × 2) was added to the system for extraction. The combined organic phase was dried over anhydrous sodium sulfate, filtered and distilled under reduced pressure, and separated by column chromatography. The eluent was dichloromethane / methanol (volume ratio 20 / 1), and the main molecule, i.e., reactant 2, was obtained:

[0085] The H NMR results of the reactant 2 in this example are as follows:

[0086] 1 H NMR (600MHz, CDCl3) δ (ppm): 6.96 (s, 1H), 6.90-6.86 (m, 2H), 4.60 (s, 2H), 4 .20-4.18(m,4H),3.93-3.88(m,4H),3.80-3.77(m,4H),3.72-3.65(m,16H).

[0087] Reactant 1 (10 mmol, 3.4 g) and reactant 2 (10 mmol, 3.6 g) were added to a 500 mL round-bottom flask, 50 mL of dichloromethane (DCM) was added to dissolve, and refluxed at 45° C. for 24 h. The reaction was stopped, and the solvent was dried to obtain a mechanical interlocking unit.

[0088] The NMR comparison results of the mechanical interlocking unit and reactant 2 are as follows: Figure 1 As shown, the successful synthesis of mechanically interlocked units is demonstrated.

[0089] Synthesis of photoresponsive polymer network A based on azo motifs and mechanical interlocking structure:

[0090] Under nitrogen, the azo element (0.15 mmol), polytetrahydrofuran (0.25 mmol), hexamethylene diisocyanate (0.64 mmol) and reaction solvent DCM (2 mL) of this embodiment were added to the reaction bottle, and a drop of dibutyltin dilaurate was used as a catalyst. The system was stirred for 1 day, and then the mechanical interlocking unit (0.16 mmol) of this embodiment dissolved in a small amount of DCM (0.5 mL) was added to the above system, and stirring was continued for one day. The evenly stirred mixed solution was poured into a mold and vacuum dried for 12 h to obtain a photoresponsive polymer network A based on azo elements and mechanical interlocking structure.

[0091] Comparative Example 1

[0092] Under nitrogen, the azo element (0.15 mmol), polytetrahydrofuran (0.25 mmol), hexamethylene diisocyanate (0.64 mmol) and reaction solvent DCM (2 mL) of Example 1 were added to the reaction bottle, and a drop of dibutyltin dilaurate was used as a catalyst. The system was stirred for 1 day, and then 1,1,1-tri(hydroxymethyl)ethane (0.16 mmol) dissolved in a small amount of DCM (0.5 mL) was added to the above system, and stirring was continued for one day. The uniformly stirred mixed solution was poured into a mold and vacuum dried for 12 h to obtain a control polymer network A.

[0093] The polymer network A of Example 1 ( Figure 2 a) and the control polymer network A of Comparative Example 1 ( Figure 2 b) Stress-strain test results at a stretching rate of 100 mm / min before and after illumination. Figure 2 The post-illumination stretching test herein refers to the stretching test of the polymer network A of Example 1 and the control polymer network A of Comparative Example 1 after being irradiated with a 365 nm light source for 1 hour.

[0094] Example 2

[0095] Synthesis of photoresponsive polymer network B based on azo motifs and mechanical interlocking structure:

[0096] Under nitrogen, the azo element (0.20 mmol) of Example 1, polytetrahydrofuran (0.20 mmol), hexamethylene diisocyanate (0.64 mmol) and reaction solvent DCM (2 mL) were added to the reaction bottle, and a drop of dibutyltin dilaurate was used as a catalyst. The system was stirred for 1 day, and then the mechanical interlocking unit (0.16 mmol) of Example 1 dissolved in a small amount of DCM (0.5 mL) was added to the above system, and stirring was continued for one day. The evenly stirred mixed solution was poured into a mold and vacuum dried for 12 h to obtain a photoresponsive polymer network B based on azo elements and mechanical interlocking structure.

[0097] Comparative Example 2

[0098] Under nitrogen, the azo element (0.20 mmol) of Example 1, polytetrahydrofuran (0.20 mmol), hexamethylene diisocyanate (0.64 mmol) and reaction solvent DCM (2 mL) were added to the reaction bottle, and a drop of dibutyltin dilaurate was used as a catalyst. The system was stirred for 1 day, and then 1,1,1-tri(hydroxymethyl)ethane (0.16 mmol) dissolved in a small amount of DCM (0.5 mL) was added to the above system, and stirring was continued for one day. The uniformly stirred mixed solution was poured into a mold and vacuum dried for 12 h to obtain a control polymer network B.

[0099] Polymer network B of Example 2 ( Figure 3 a) and the control polymer network B of Comparative Example 2 ( Figure 3 b) Stress-strain test results at a stretching rate of 100 mm / min before and after illumination. Figure 3 The post-illumination stretching test herein refers to the stretching test of the polymer network B of Example 2 and the control polymer network B of Comparative Example 2 after being irradiated with a 365 nm light source for 1 hour.

[0100] Example 3

[0101] Synthesis of photoresponsive polymer network C based on azo motifs and mechanical interlocking structures:

[0102] Under nitrogen, the azo moiety (0.25 mmol), polytetrahydrofuran (0.15 mmol), hexamethylene diisocyanate (0.64 mmol) and reaction solvent DCM (2 mL) of Example 1 were added to the reaction bottle, and a drop of dibutyltin dilaurate was used as a catalyst. The system was stirred for 1 day, and then the mechanical interlocking unit (0.16 mmol) of Example 1 dissolved in a small amount of DCM (0.5 mL) was added to the above system, and stirring was continued for one day. The evenly stirred mixed solution was poured into a mold and vacuum dried for 12 h to obtain a photoresponsive polymer network C based on azo motifs and mechanical interlocking structures.

[0103] Comparative Example 3

[0104] Under nitrogen, the azo element (0.25 mmol) of Example 1, polytetrahydrofuran (0.15 mmol), hexamethylene diisocyanate (0.64 mmol) and reaction solvent DCM (2 mL) were added to the reaction bottle, and a drop of dibutyltin dilaurate was used as a catalyst. The system was stirred for 1 day, and then 1,1,1-tri(hydroxymethyl)ethane (0.16 mmol) dissolved in a small amount of DCM (0.5 mL) was added to the above system, and stirring was continued for one day. The uniformly stirred mixed solution was poured into a mold and vacuum dried for 12 h to obtain a control polymer network C.

[0105] The polymer network C of Example 3 ( Figure 4 a) and the control polymer network C of Comparative Example 3 ( Figure 4 b) Stress-strain test results at a stretching rate of 100 mm / min before and after illumination. Figure 4 The post-illumination stretching test herein refers to the stretching test of the polymer network C of Example 3 and the control polymer network C of Comparative Example 3 after being irradiated with a 365 nm light source for 1 hour.

[0106] Example 4

[0107] First, the photoresponsive polymer network C based on azo motifs and mechanical interlocking structure in Example 3 was subjected to swelling experiments in 6 solvents (acetone, N,N-dimethylformamide (DMF), chloroform, dichloromethane (DCM), acetonitrile, and tetrahydrofuran (THF). Figure 5 ), the results showed that the network only swelled but did not dissolve, indicating that the synthesis of the cross-linked network was successful.

[0108] Subsequently, the three polymer networks AC containing different proportions of azo photosensitive units in Examples 1-3 were subjected to stretching tests before and after irradiation. The results are as follows: Figures 2 to 4 As shown in Table 1. For the photoresponsive polymer network based on azo motifs and mechanical interlocking structures, whether before or after illumination, as the azo content increases, the material elongation at break decreases, the Young's modulus increases, and the toughness decreases. For the control polymer network, the initial elongation at break is short, the modulus is high, and the toughness is low; after illumination, the modulus decreases, the elongation at break increases, the toughness increases, and it is higher than the cycloalkane group, that is, it is softer and more elastic after illumination. When the network is exposed to light, whether it is the polymer network of the present invention or the control polymer network, the azo motif in the system is cis. For the control polymer network, since it does not contain a mechanical interlocking unit (slip ring motif), cis azo is not conducive to pi-pi stacking after illumination, and the rigidity decreases; and the photoresponsive polymer network based on azo motifs and mechanical interlocking structures contains a slip ring structure, and the limited motion of the slip ring plays a more dominant role. After illumination, the ring sliding distance is greatly limited, so the rigidity is improved after illumination. Before illumination, the elongation at break of the control polymer network is smaller than that of the polymer network of the present invention. This is because the system is relatively rigid and the sliding of the ring contributes greatly to the stretchability. After illumination, the elongation at break of the control polymer network is greater than that of the polymer network of the present invention. This is because the system is relatively flexible and the sliding space of the ring is limited. Therefore, the sliding advantage of the sliding node compared with the fixed node is weakened, and the crown ether with larger steric hindrance weakens the hydrogen bonds between the polyurethane units, further reducing the elongation at break.

[0109] Table 1

[0110]

[0111] Subsequently, the changes in strain, Young's modulus, and toughness of the three photoresponsive polymer networks AC based on azo motifs and mechanical interlocking structures in Examples 1-3 before and after illumination were compared ( Figure 6 ), it was found that the change value of photoresponsive polymer network C was the most obvious, which may be due to the fact that the proportion of azo units in photoresponsive polymer network C was the highest, so the difference before and after illumination was the most obvious. Therefore, the following tests were compared with photoresponsive polymer network C and control polymer network C.

[0112] Example 5

[0113] Optical tests of azo moieties and polymer network C:

[0114] 1) Take 4 mL of DMF to prepare a blank solution, and measure the baseline and blank using a UV spectrophotometer.

[0115] 2) Prepare the test solution by mixing 50 μL of azo element or polymer network solution with 4 mL of DMF. Measure the ultraviolet absorption spectrum of the solution with an ultraviolet spectrophotometer in the wavelength range of 600 nm to 200 nm to obtain a curve of the absorption value (Abs.) versus wavelength (nm).

[0116] 3) After the solution was irradiated with an ultraviolet LED lamp for 5 minutes, the ultraviolet absorption spectrum of the solution was measured with an ultraviolet spectrophotometer under the same conditions.

[0117] 4) Place the solution under light or darkness for 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min, and measure the UV absorption spectrum of the solution using a UV spectrophotometer under the same conditions.

[0118] The azo photosensitive unit solution and the polymer solution of Example 3 were irradiated with an ultraviolet LED lamp for 5 minutes, and the ultraviolet absorption spectra of the solutions were measured with an ultraviolet spectrophotometer under the same conditions. The two solutions were then left to stand under light or darkness for 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, and 60 minutes, and the ultraviolet absorption spectra of the solutions were measured with an ultraviolet spectrophotometer under the same conditions. The results are as follows: Figure 7 As shown. Under ultraviolet light, the planar nonpolar trans isomer of azobenzene isomerizes to the metastable cis form. The cis-to-trans isomerization occurs spontaneously. The isomerization rate is slow in the dark and becomes faster under visible light. And the isomerization rate from trans to cis and from cis to trans can be repeated. After adding azo photosensitive units to the polymer network, the polymer network can also isomerize and transisomerize like azo small molecules.

[0119] Example 6

[0120] The polymer network C of Example 3 of the present invention was subjected to cyclic stress-strain testing in a wide range of maximum applied strains from 25% to 200% before and after illumination ( Figure 8 a- Figure 8 b). Regardless of whether before or after illumination, the polymer network of the present invention exhibits obvious hysteresis, which is mainly attributed to the dissociation of the abundant hydrogen bonds generated by the PU segments. In addition, by comparing the energy dissipation value and damping capacity (ratio of energy dissipation to input energy) of polymer network C before and after illumination, analysis shows that the energy dissipation value and damping energy of polymer network C before illumination are greater than those after illumination. This is because the sliding of the azo cis-anti ring plays an important role. After illumination, the azo is in a cis conformation, which blocks the sliding of the ring, thereby weakening the energy dissipation capacity of the polymer network ( Figure 8 c- Figure 8 d).

[0121] To further illustrate the problem, the control polymer network C of Comparative Example 3 was also subjected to cyclic stress-strain tests in a wide range of maximum applied strains from 25% to 200% before and after illumination ( Fig. 9 a- Fig. 9 b). Comparison of the damping energy results with a strain of 25% shows that ( Fig. 9 c) For the polymer network of the present invention, the damping energy before illumination is greater than the damping energy after illumination, while for the control polymer network, the damping energy does not change much before and after illumination. Due to their same PU composition and azo content, the damping capacity may be related to the sliding space of the ring.

[0122] The above results show that the photoresponsive polymer network based on azo motifs and mechanical interlocking structures can regulate the sliding distance of the ring through the cis-trans isomerization of azo and change the mechanical properties of the material ( Fig.10 ).

[0123] In summary, the present invention uses ultraviolet absorption spectroscopy to prove that under ultraviolet (UV) light irradiation, the planar non-polar trans isomer of azobenzene isomerizes to a metastable cis form, and the cis→trans isomerization occurs spontaneously and can be accelerated under visible light; through mechanical testing, it is proved that the synthesized polymer network has elastic toughness and tensile resistance, and its mechanical properties can be regulated by light stimulation.

[0124] The present invention compares the mechanical properties of materials before and after light response, and proposes a new model of mechanical property change. Through the cis-trans isomerization of azo units, the sliding space of the ring in the system is adjusted (the cis-azo has a large steric hindrance and the ring cannot pass; the trans-azo has a small steric hindrance and the ring can pass), thereby adjusting the mechanical properties of the polymer network.

[0125] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A photoresponsive polymer network based on azo motifs and mechanical interlocking structures, characterized in that: It is obtained by reacting raw materials including azo moieties, polytetrahydrofuran, hexamethylene diisocyanate and mechanical interlocking units; The azo group is selected from at least one of the compounds having the following structure: Wherein, n is 1 to 10; The mechanical interlocking unit has the following structure:

2. The photoresponsive polymer network according to claim 1, characterized in that The preparation method of the azo element comprises: The 4,4'-dihydroxyazobenzene, monomer I, potassium carbonate and solvent are mixed for reaction, and after the reaction, the solvent is removed, and the mixture is extracted and purified, and column chromatography is performed to obtain the azo moiety; The monomer I is selected from at least one of the compounds having the following structure: Wherein, n is 1 to 10; In the preparation method of the azo unit: The usage ratio of 4,4'-dihydroxyazobenzene, monomer I, potassium carbonate and solvent is 1mmol:1.2-1.5mmol:2-4mmol:4-8mL; The solvent includes at least one of N,N-dimethylformamide and water; The temperature of the mixed reaction is room temperature to 140°C; The mixing reaction time is 12 to 24 hours; The extraction solvent used in the extraction purification includes dichloromethane; The eluents used in the column chromatography analysis are dichloromethane and methanol; in the eluent, the volume ratio of the dichloromethane to the methanol is 20:

1.

3. The photoresponsive polymer network according to claim 1, characterized in that The number average molecular weight of the polytetrahydrofuran is 1000 to 2000 g / mol; In the raw materials, the total molar number of hydroxyl groups of the azo unit, polytetrahydrofuran and mechanical interlocking units is equal to the total molar number of NCO groups of hexamethylene diisocyanate; In the raw materials, based on the total molar number of azo moieties, polytetrahydrofuran and mechanical interlocking units as 100%, the proportion of the azo moieties is 25% to 45%, and the proportion of the mechanical interlocking units is 25% to 35%.

4. The photoresponsive polymer network according to claim 1, characterized in that The preparation method of the mechanical interlocking unit comprises: The reactant 1 and the reactant 2 are mixed in a solvent for reaction, and the solvent is removed after the reaction is completed to obtain the mechanical interlocking unit; The reactant 1 has the following structure: The reactant 2 has the structure shown below:

5. The photoresponsive polymer network according to claim 4, characterized in that In the preparation method of the mechanical interlocking unit: The solvent includes dichloromethane; The temperature of the mixed reaction is 40-50°C; The mixing reaction time is 12 to 24 hours.

6. The photoresponsive polymer network according to claim 4, characterized in that The preparation method of the reactant 1 comprises: 4-Hydroxybenzaldehyde and 5-bromo-1-pentanol react to obtain compound 3 having the following structure: Compound 3 reacts with 6-hydroxyhexylamine to obtain a Schiff base, which is reduced with sodium borohydride and then added with hydrochloric acid to produce a precipitate. The solid is separated from the solid and added to a saturated ammonium hexafluorophosphate solution, and extracted and purified to obtain the reactant 1.

7. The photoresponsive polymer network according to claim 4, characterized in that The preparation method of the reactant 2 includes the following synthetic route: The preparation method of the reactant 2 comprises the steps of: (1) heptaethylene glycol reacts with p-toluenesulfonyl chloride to obtain intermediate 4; (2) The intermediate product 4 reacts with 3,4-dihydroxybenzaldehyde to obtain the intermediate product 5, and the intermediate product 5 is reduced with sodium borohydride to obtain the reactant 2.

8. The method for preparing a photoresponsive polymer network according to any one of claims 1 to 7, characterized in that: include: Under an inert atmosphere, an azo unit, polytetrahydrofuran, hexamethylene diisocyanate, a reaction solvent and an optionally added catalyst are mixed and reacted for a period of time, and then a mechanical interlocking unit is added to continue the reaction. The reaction mixture is vacuum dried to obtain the photoresponsive polymer network.

9. The preparation method according to claim 8, characterized in that: The inert atmosphere is a nitrogen atmosphere; The reaction solvent is an organic solvent; the organic solvent includes at least one of dichloromethane, tetrahydrofuran, acetonitrile and acetone; The catalyst includes dibutyltin dilaurate; In the method for preparing the photoresponsive polymer network, the reaction temperature is 30-50°C.

10. Use of the photoresponsive polymer network according to any one of claims 1 to 7 in photosensitive materials, characterized in that: The tensile properties of the photosensitive material change with the change of light conditions. The cis-trans configuration of the azo moiety is regulated by changing the light conditions, thereby controlling the sliding ability of the ring in the mechanical interlocking unit, thereby achieving the adjustment of the tensile properties.

Citation Information

Cited By

  • Mechanical interlocking polymer network with photoresponsiveness as well as preparation method and application thereof

    CN119875077A

  • Mechanically interlocked polymer networks with photoresponsiveness and preparation methods and applications thereof

    CN119875077B